ROLE OF MRI IN EVALUATION OF ACUTE VISUAL SYMPTOMS-AN INSTITUTIONAL STUDY - Gandi Prem Kumar; Goolla Dhivya; Dr. S. Shruthi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
AIMS AND OBJECTIVES:• To define and analyze MRI findings for characterization of various lesions causing acute visual syndromes(AVS).• To diagnose lesions based on the MRI findings by correlating with provided clinical• To correlate the MRI diagnosis with final MATERIALS & METHODS:• This study was conducted in Department of Radiology and Imageology at Nizam’s institute of medical The study was approved by the Institutional Ethics Committee. This is a prospective study, conducted over a period of 17 months (December 2022-April 2024)• This study included 47 patients irrespective of their age who presented with symptoms and signs of acute visual syndromes underwent MR imaging features of various lesions were evaluated. The provided relevant clinical data was collected from the patients was reviewed. MRI diagnosis was given based on the imaging characteristics and provided clinical data.• Possible explanation was drawn to explain the symptoms and treatment response based on MRI features. The imaging features were correlated with final RESULTS• The overall mean age of the study population is 5 years with most commonly observed age group 40-50 years. We observed male preponderance in this study with maximum number of both males and females in inflammatory lesions. Inflammatory lesions were most prevalent in this study contributing to 47.8% (n=23) followed by space occupying and vascular lesions (19.5%, n=9), infections (17.3%, n=8) and miscellaneous lesions (Idiopathic intra cranial hyper tension(IIH) & posterior reversible encephalopathy syndrome) (15.1%, n=7).• Overall most common pathology was optic neuritis(1) contributing to 32 %(n=15) of the study population followed by Tolosa hunt syndrome (12.7%. n=6), pituitary macro adenoma (8.5%, n=4), posterior reversible encephalopathy syndrome (PRES) (8.5%, n=4), tuberculosis (8.5%, n=4), fungal infections (6.3%, n=3), idiopathic intracranial hypertension (6.3%, n=3), sarcoidosis (4.2%, n=2), suprasellar pilocytic astrocytoma (2.1%. n=1) and left cavernous ICA aneurysm (2.1%, n=1).• Out of 47 patients MRI detected abnormality in 41 patients (87%). MRI could not detect the pathology in 6 patients (12.7%), all these were patients of optic neuritis. The given single specific diagnosis based on MRI was correlated with final diagnosis in 37 patients (78%), two differential diagnoses were given in four (8.5%) Out four patients first differential diagnosis was correlated with final diagnosis in three patients, second differential diagnosis was correlated with final diagnosis in one patient of pilocytic astrocytoma. In this study the overall sensitivity of MRI in detecting the lesions causing acute visual syndromes is 88.67% whereas specificity is 100%. Except for optic neuritis sensitivity and specificity of MRI in detecting the lesions is 100%. Conclusion• Conclusion of the present study is that while the symptomatology of acute visual syndrome is often nonspecific and confusing, MRI imaging adds sensitivity and specificity to the physical Because of its better soft tissue resolution, characteristic signal intensity pattern of certain lesions and lack of ionizing radiation hazards, MRI should be the imaging modality of choice for patients .